Polyester film and use thereof

By developing a polyester film with excellent mechanical properties under high temperature conditions, the problem of existing films being easily deformed under high temperature environments is solved, and the image stability and portability of foldable displays are achieved.

CN119866356APending Publication Date: 2025-04-22TOYOBO CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380065275.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-09-07
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing polyester films are prone to deformation under high temperature environments, resulting in distortion of the image of the folded display, and poor durability after repeated bending.

Method used

A polyester film has been developed, with a tan δ of 0.040 or less at 100°C, a thickness of 10 to 125 μm, a high temperature holding angle at 60°C, and a high temperature holding angle at 85°C, and an excellent density and easy adhesive layer.

Benefits of technology

The polyester film maintains good mechanical properties under high temperature conditions, does not easily cause deformation, and reduces image disorder in the folded part. It is suitable for folded displays, providing beautiful images and high portability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119866356A_ABST
    Figure CN119866356A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a polyester film for a folding-type display, which has excellent mass productivity and heat resistance, suppresses the occurrence of image disorder in a folded portion after repeated bending, and suppresses the occurrence of cracks in the folded portion. The present invention relates to a polyester film having a tan [delta] of 0.040 or less at 100 DEG C as determined by a dynamic viscoelasticity measurement by stretching in at least one of the longitudinal direction and the width direction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyester film having excellent heat resistance and bending resistance, a polyester film for a foldable display, a hard-coated film for a foldable display, a foldable display and a portable terminal device, and in particular to a back protective film for a foldable display which is not prone to image disturbance caused by deformation of the film even when folded repeatedly, a foldable display and a portable terminal device. Background Art

[0002] As the lightweighting of portable terminal devices is promoted, portable terminal devices represented by smartphones have become widely popular. Portable terminal devices are required to have various functions, but also convenience. Therefore, the popular portable terminal devices are required to be easy to operate with one hand and to be stored in the pocket of clothes, so a small screen size of about 6 inches is required.

[0003] On the other hand, tablet terminals with a screen size of 7 to 10 inches are expected to have high functionality, including applications based not only on video content and music, but also applications based on business use, drawing, reading, etc. However, they cannot be operated with one hand and have poor mobility, which poses a problem in terms of convenience.

[0004] In order to achieve this, a method of connecting a plurality of displays to make them compact has been proposed (see Patent Document 1). However, in the invention of Patent Document 1, since the frame portion remains, the image is interrupted, and the reduction in visibility becomes a problem, and it has not yet been popularized.

[0005] On the other hand, in recent years, portable terminals equipped with flexible displays or foldable displays have been proposed. In this case, the image will not be interrupted, and the portable terminal device equipped with a large-screen display can be conveniently carried.

[0006] Here, regarding existing displays and portable terminal devices that do not have a folding structure, the surface of the display can be protected by non-flexible raw materials such as glass. However, in a foldable display, in the case of a display that forms one side through a folded portion, a hard coating film that is flexible and can protect the surface must be used. Plastic films are excellent in flexibility, and polyester films are suitable in terms of mechanical properties, optical properties, price, etc. However, for existing polyester films, when the device itself has heat during operation or when the device is placed in a high temperature environment such as in a car, it may easily cause deformation that distorts the image.

[0007] Furthermore, in a foldable display, the folded portion is repeatedly bent, so there is a problem that the film of this portion is deformed over time, causing the image of the folded portion displayed in the display to be distorted. In addition, in a foldable display, a film is used not only in the surface protection film, but also in various parts such as polarizing plates, phase difference plates, touch panel substrates, substrates of display elements such as organic EL, and protective components on the back, and these films are also required to be durable against repeated folding.

[0008] Therefore, a method of partially changing the film thickness has also been proposed (see Patent Document 2). However, the invention of Patent Document 2 has a problem that the manufacturing process becomes complicated in order to change the film thickness, and mass productivity is poor.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2010-228391

[0012] Patent Document 2: Japanese Patent Application Publication No. 2016-155124

[0013] Patent Document 3: International Publication No. 2018 / 150940 Summary of the invention

[0014] Problem that the invention aims to solve

[0015] In addition, a method of adjusting the refractive index of a polyester film in a bending direction has been proposed (see Patent Document 3). However, this film may not be usable in applications requiring higher reliability (high temperature region).

[0016] The present invention aims to solve the problems existing in the components of existing displays as described above, and provides a polyester film for a foldable display in order to provide a foldable display having excellent heat resistance, excellent mass producibility, and less concern about disturbance of the image displayed in the folded portion after repeated bending, as well as a portable terminal device equipped with such a foldable display.

[0017] Furthermore, the present invention intends to provide a polyester film for a foldable display in which creases are less likely to be generated at the folded portion even when folded in a high temperature region.

[0018] Solutions for solving problems

[0019] The present invention typically includes the following configurations.

[0020] 1. A polyester film, wherein tan δ at 100° C., as measured by dynamic viscoelasticity under tension, in at least one of a longitudinal direction and a width direction is 0.040 or less.

[0021] 2. The polyester film according to claim 1, which has a thickness of 10 to 125 μm, a high temperature retention angle of 100° or more at 60°C and a high temperature retention angle of 80° or more at 85°C in either the longitudinal direction or the width direction.

[0022] Here, the high temperature holding angle refers to the angle of the fold produced when the polyester film is fixed under heating at 60° C. or 85° C. for 18 hours so that strain of 1.7% is generated on both surfaces of the bent portion.

[0023] 3. The polyester film according to item 1 or 2, which is used for a foldable display.

[0024] 4. The polyester film according to any one of items 1 to 3, which has a density of 1.349 g / cm 3 above.

[0025] 5. The polyester film according to any one of Items 1 to 4, wherein the polyester is polyethylene naphthalate.

[0026] 6. The polyester film for foldable displays according to any one of Items 1 to 5, comprising an easily adhesive layer on at least one surface of the polyester film.

[0027] 7. A foldable display comprising the polyester film according to any one of 1 to 6, wherein the polyester film is arranged as a single back protective film that is continuous through a folded portion of the foldable display.

[0028] 8. A portable terminal device comprising the foldable display described in item 7.

[0029] Effects of the Invention

[0030] The polyester film of the present invention maintains good mass production performance and is not easily deformed after repeated folding under high temperature conditions, and is not easily disturbed in the folded portion of the display even when used in a foldable display. A portable terminal device equipped with a foldable display using the polyester film described above provides a beautiful image even after repeated folding, is rich in functionality, and has excellent convenience such as portability. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A schematic diagram for illustrating a foldable display and a bending radius when folded.

[0032] Figure 2 It is a schematic diagram for showing the bending direction of the polyester film in the present invention.

[0033] Figure 3It is a schematic diagram for explaining the method of measuring the high temperature holding angle in the bending direction.

[0034] Figure 4 An enlarged schematic diagram showing a sample film (reference numeral 3) sandwiched between two PTFE plates.

[0035] Figure 5 Schematic diagram showing an outwardly curved foldable smartphone and a foldable display. DETAILED DESCRIPTION

[0036] (monitor)

[0037] The display in the present invention refers to all display devices, and the types of displays include LCD, organic EL display, inorganic EL display, LED, FED, etc. For example, LCD, organic EL display, and inorganic EL display having a bendable structure are preferred. Organic EL display and inorganic EL display are more preferred in terms of reducing the layer structure, and organic EL display is particularly preferred in terms of wide color gamut.

[0038] (Foldable Display)

[0039] For a foldable display, a continuous display can be folded into two when carried. By folding, the size is reduced by half, and mobility can be improved. The bending radius of the foldable display is preferably less than 5 mm, and more preferably less than 3 mm. When the bending radius is less than 5 mm, thinning becomes possible in the folded state. It can be said that the smaller the bending radius, the better. According to the foldable display of the present invention, even if it is used with such a bending radius, the occurrence of creases on the polyester film can be suppressed.

[0040] The bending radius of the foldable display is preferably 0 to 5 mm, more preferably 0 to 3 mm. If the bending radius is 5 mm or less, thinning in the folded state becomes possible. The smaller the bending radius, the better, and it can be 0.1 to 5 mm, 0.1 to 3 mm, 0.5 to 3 mm, 0.5 to 5 mm, 1 to 5 mm. Even if the bending radius is 1 to 5 mm, it can achieve a practically sufficient thinness in the folded state compared to a display without a folding structure.

[0041] The bending radius when folded is Figure 1 In the foldable display 1 in the schematic diagram of , the value obtained by measuring the position indicated by reference numeral 11 is the radius of the inner side of the folded portion when folded. It should be noted that the surface protection film described below may be located outside or inside the fold of the foldable display.

[0042] In addition, the foldable display may be folded in three or four ways, or may be a so-called rollable type, all of which are included in the scope of the foldable display described in the present invention.

[0043] In addition, the polyester film of the present invention can be used not only Figure 1 A foldable display with improved bending in length and improved bending in width is shown.

[0044] The foldable display can be either outwardly curved or inwardly curved. For an inwardly curved foldable display, the display is located inside when folded, and the display is usually not visually recognizable in the folded state. For an outwardly curved foldable display, the display is located outside when folded, and the display can be visually recognizable in the folded state ( Figure 5 ). The polyester film of the present invention can be used in any manner. In addition, in any foldable display that is curved outward or inward, the polyester film of the present invention can be arranged on either the outside or the inside of the display, or on both the outside and the inside. The polyester film of the present invention is not prone to creases even with a small bending radius, and therefore can be used in such various manners.

[0045] The polyester film for a foldable display of the present invention can be used in any part as long as it is a constituent member of a foldable display. Figure 5 , a diagram schematically showing the structure of a foldable display is shown. Below, taking an organic EL display as an example, a representative structure of a foldable display and a portion in which the polyester film of the present invention can be used are described. It should be noted that, below, the polyester film for a foldable display of the present invention is sometimes referred to as the polyester film of the present invention.

[0046] (Foldable organic EL display)

[0047] The foldable organic EL display has an organic EL component as an essential component, but a circular polarizing plate, a touch panel component, a surface protection film, a back protection film, etc. may be further provided as needed.

[0048] (Organic EL components)

[0049] The general structure of an organic EL component includes: electrode / electron transport layer / luminescent layer / hole transport layer / transparent electrode. As a substrate for providing an electrode, and further providing an electron transport layer, a luminescent layer, a hole transport layer, and a transparent electrode, the polyester film of the present invention can be used. In particular, it can be preferably used as a substrate for a transparent electrode. In this case, the substrate film requires high barrier properties against water vapor and oxygen, so it is preferred that a barrier layer such as a metal oxide layer is provided on the polyester film of the present invention. In order to improve the barrier properties, a plurality of barrier layers can be provided, or a plurality of polyester films provided with barrier layers can be used.

[0050] (Touch Panel Assembly)

[0051] The portable terminal device preferably has a touch panel. When an organic EL display is used, a touch panel component is preferably arranged on the upper part of the organic EL display or between the organic EL component / circular polarizer. The touch panel component has a transparent substrate such as a film and a transparent electrode arranged thereon. The polyester film of the present invention can be used as the transparent substrate. When used as a transparent substrate of a touch panel, a hard coating layer and a refractive index adjustment layer are preferably provided on the polyester film.

[0052] (Circular polarizing plate)

[0053] The circular polarizer reflects external light from the components inside the display to suppress the degradation of image quality. The circular polarizer has a linear polarizer and a phase difference plate. The linear polarizer has a protective film on the surface of at least the visual recognition side. The surface of the linear polarizer opposite to the visual recognition side may also have a protective film, and the phase difference plate may also be directly laminated on the linear polarizer. The phase difference plate uses a resin film with a phase difference such as polycarbonate, cyclic olefin, etc., and a phase difference layer formed by a liquid crystal compound is provided on the resin film. The polyester film of the present invention can be used as a polarizer protective film and a resin film of a phase difference plate. In these cases, the polyester film of the present invention preferably has a slow axis direction of the polyester film parallel or orthogonal to the absorption axis direction of the polarizer. It should be noted that for this parallel or orthogonal, a deviation of up to 10 degrees, preferably up to 5 degrees, is allowed.

[0054] (Surface protection film)

[0055] If an impact is applied to the display from above, there is a concern that the circuits of the organic EL components and touch panel components may be broken. In order to prevent this phenomenon, a surface protection film is provided in most cases. The polyester film of the present invention can be used as the surface protection film. The surface protection film includes: a cover window that is installed on the outermost surface of the display; and a back film. The polyester film of the present invention can be used as any film. The back film is a film that is attached to the cover window by the manufacturer during the manufacturing process to protect the cover window, and a replaceable film that is attached to the cover window by the user. When the polyester film of the present invention is used as a surface protection film, it is preferably laminated with a hard coating layer on at least the surface side of the polyester film. The hard coating layer is located on the visual recognition side, and the polyester film is provided on the surface of the foldable display. It should be noted that the hard coating layer can also be provided on both sides of the polyester film.

[0056] (Back protection film)

[0057] It is also preferred that a protective film is also provided on the back side of the display. Specifically, the structure is such that an adhesive layer is provided on the non-visual recognition side of the organic EL element and a protective film is laminated thereto. The polyester film of the present invention can be used as the protective film on the back side.

[0058] The polyester film of the present invention may be used for purposes other than the above as long as it is used in a foldable portion of a constituent member of a foldable display.

[0059] Among these, the polyester film of the present invention is preferably used for a window surface protection film, a surface protection film for aftermarket products, a substrate film of a touch panel assembly, and a back protection film. It is preferably used for a window surface protection film, and a surface protection film for aftermarket products.

[0060] In addition, in the foldable display, the polyester film of the present invention need not be used in all of the above-mentioned films. In the foldable display, in addition to the polyester film of the present invention, appropriate polyimide films, polyamide films, polyamideimide films, polyester films other than the polyester film of the present invention, polycarbonate films, acrylic films, triacetyl cellulose films, cycloolefin polymer films, polyphenylene sulfide films, polymethylpentene films, etc. can be appropriately selected and used according to the application and purpose of use.

[0061] (Polyester film)

[0062] The polyester film of the present invention may be a single-layer film or a multilayer film having two or more layers, and each layer constituting the multilayer film may contain the same polyester resin or different polyester resins. In addition, the multilayer film may have a super multilayer structure formed by alternately and repeatedly stacking different layers. The multilayer film may have, for example, a structure of 2 to 30 layers or a structure of 2 to 20 layers. The polyester film may be a single-layer film formed of one or more polyester resins. When two or more polyester resins are used, the polyester film may be a multilayer film having a super multilayer structure or other multilayer films.

[0063] Examples of the polyester resin used in the polyester film include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, such as polyethylene 2,6-naphthalate, or copolymers containing these resins as the main components. Among them, polyethylene naphthalate films are preferred, and stretched polyethylene naphthalate films are particularly preferred, from the perspectives of mechanical properties, heat resistance, and transparency.

[0064] One form of the polyester film contains polyethylene naphthalate resin as a main component (e.g., more than 50% by mass). The polyester film may also contain other polyester resins, the content of which is relative to the mass of the polyester film 100% by mass, for example, less than 50% by mass, less than 40% by mass, less than 10% by mass, preferably less than 5% by mass, more preferably less than 5% by mass. By making the content of other polyester resins less than 5% by mass, the crystallinity of the polyester film can be maintained at a high level, and the high temperature holding angle can be well maintained. When the polyester film contains other polyester resins, the content thereof can be relative to the mass of the polyester film 100% by mass, for example, 0.1% by mass or more and less than 50% by mass, 0.1 to 40% by mass, 0.1 to 10% by mass, 0.1 to 5% by mass, 0.1% by mass or more and less than 5% by mass, etc.

[0065] On the other hand, the content of the polyethylene naphthalate resin in the polyester film may be more than 50 mass %, 60 mass % or more, 90 mass % or more, preferably 95 mass % or more, and more preferably more than 95 mass % based on the mass of the polyester film.

[0066] In one embodiment, the ratio of polyethylene naphthalate in the raw material ratio of the polyester film is 100% by weight.

[0067] It should be noted that, in the present invention, the polyester film may contain a plurality of polyethylene naphthalate having different properties.

[0068] By increasing the proportion of polyethylene naphthalate, the deformation of the polyester film after folding in a high temperature region is suppressed, and image disturbance at the folded portion of the display can be suppressed. Furthermore, a portable terminal device equipped with a foldable display using the polyester film of the present invention provides a beautiful image and is a device with excellent convenience such as rich functionality and portability.

[0069] When a polyester copolymer is used in a polyester film, as the dicarboxylic acid component of the polyester, for example, aliphatic dicarboxylic acids such as adipic acid and sebacic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalene dicarboxylic acid; polyfunctional carboxylic acids such as trimellitic acid and pyromellitic acid. In addition, as the diol component of the polyester, for example, fatty acid diols such as ethylene glycol, diethylene glycol, 1,4-butanediol, propylene glycol, and neopentyl glycol, aromatic diols such as terephthalyl alcohol, alicyclic diols such as 1,4-cyclohexanedimethanol, and polyethylene glycols with an average molecular weight of 150 to 20,000 can be mentioned. The preferred mass ratio of the copolymer component in the polyester copolymer is less than 3 mass%. When it is less than 3 mass%, the film strength, transparency, and heat resistance can be maintained, which is preferred.

[0070] In addition, the intrinsic viscosity of the resin pellets used as the raw material of the polyester film is preferably in the range of 0.40 to 1.0 dl / g. If the intrinsic viscosity is 0.40 dl / g or more, the impact resistance of the obtained film is improved, and it is not easy to cause the internal circuit of the display to be disconnected due to external impact, which is preferred. If the intrinsic viscosity is 1.00 dl / g or less, the filter pressure of the molten fluid does not increase excessively, making the film production stable and easy to operate, which is preferred.

[0071] For example, when the polyester film includes a plurality of resin pellets, the intrinsic viscosity of all of the plurality of resin pellets may be in the range of 0.40 to 1.0 dl / g, and at least one of the pellets may have an intrinsic viscosity in the range of 0.40 to 1.0 dl / g. In one embodiment, when the polyester film includes a plurality of resin pellets, the intrinsic viscosity of the resin pellets serving as the main component is in the range of 0.40 to 1.0 dl / g.

[0072] In addition, the intrinsic viscosity of the polyester film is preferably in the range of 0.40 to 0.95 dl / g. If the intrinsic viscosity of the film is 0.40 dl / g or more, the impact resistance of the obtained film is improved, and it is not easy to cause the internal circuit of the display to be disconnected due to external impact, which is preferred. If the intrinsic viscosity is 0.95 dl / g or less, the filter pressure of the molten fluid does not increase excessively, making the film production stable and easy to operate, which is preferred.

[0073] The thickness of the polyester film is, for example, 10 μm to 125 μm, preferably 25 μm to 100 μm. When the thickness is 10 μm or more, pencil hardness and impact resistance are improved, and when the thickness is 125 μm or less, it is advantageous for weight reduction and has excellent flexibility, processability, and operability.

[0074] The surface of the polyester film may be smooth or may have projections and depressions. When used for a cover window of a display, it is preferred to have a smooth film surface. The haze of the polyester film is preferably 3% or less, more preferably 2% or less, and particularly preferably 1.3% or less. If the haze is 3% or less, the visual recognition of the image can be improved. The lower limit of the haze is as small as possible, but for the sake of stable production, it is preferably 0.1% or more, and may be 0.3% or more. The haze may be, for example, 0.1-3%, 0.1-2%, 0.1-1.3%, 0.3-3%, 0.3-2%, 0.3-1.3%, etc.

[0075] As mentioned above, in order to reduce the haze, it is preferred that the surface roughness of the film is not too large, but from the viewpoint of operability, it may have roughness for the purpose of imparting a certain degree of slip. Such roughness can be formed by a method of mixing particles in a polyester film disposed on the surface layer, a method of coating a coating with particles on the polyester film during film formation, etc.

[0076] As a method for blending particles in a polyester film, a known method can be used. For example, particles can be added at any stage of manufacturing polyester. Preferably, a slurry in which particles are dispersed in ethylene glycol or the like is added at the stage of esterification, or after the end of the transesterification reaction and before the start of the polycondensation reaction, to promote the polycondensation reaction, thereby blending particles. In addition, particles can be blended by the following methods: a method of blending a slurry of particles dispersed in ethylene glycol or water or the like with a polyester raw material using a mixing extruder with a vent; or a method of blending dried particles with a polyester raw material using a mixing extruder, etc.

[0077] Among them, the following method is preferred as a method of mixing particles: the aggregated inorganic particles are homogeneously dispersed in a monomer solution that becomes a part of the polyester raw material, and then filtered, and the obtained substance is added to the remaining part of the polyester raw material before, during or after the esterification reaction. According to this method, since the monomer solution has a low viscosity, it is easy to homogeneously disperse the particles and filter the slurry with high precision, and when added to the remaining part of the raw material, the dispersibility of the particles is good and new aggregates are not easily generated. From the above viewpoints, it is particularly preferred to add the inorganic particles homogeneously dispersed in the remaining part of the raw material in a low temperature state before the esterification reaction and then filter.

[0078] Alternatively, the number of protrusions on the film surface can be further reduced by obtaining a polyester containing particles in advance and then kneading and extruding the pellets with pellets containing no particles (masterbatch method).

[0079] The tanδ obtained by dynamic viscoelasticity measurement based on stretching in the width direction or the length direction of the polyester film is preferably small, and the tanδ at 100°C is preferably 0 to 0.040, and more preferably 0 to 0.038. The tanδ in the dynamic viscoelasticity measurement is obtained from the ratio of the loss modulus to the storage modulus, and the smaller the tanδ, the more the film maintains elasticity. Compared with viscosity, the elasticity is high, and when the elasticity is maintained, it is not easy to cause irreversible deformation, and it is also difficult to introduce creases in terms of bending resistance.

[0080] Tanδ can also be adjusted according to the stretching ratio and temperature conditions, but it can also be adjusted more effectively by heat treatment (BTA treatment) after film formation. For example, aging and annealing treatments can be cited. As an example of annealing treatment, heating below the Tg of the polyester film, preferably at 90°C to 120°C, and more preferably at 95°C to 115°C, can be cited. By being within the above temperature range, the amorphous region can be effectively changed. At the above temperature, the following treatment is preferably performed: heating for more than 6 hours, preferably more than 12 hours, and more preferably more than 24 hours, and then returning to room temperature after more than 1 hour, preferably more than 6 hours, and more preferably more than 12 hours. As a result, the amorphous region is formed into a denser state, and by approaching the ideal state, the heat resistance is improved. In addition, by approaching the ideal state of the amorphous region, the bending resistance is also improved. Therefore, even if the stretching ratio and stretching temperature conditions during manufacturing are further expanded, a film with excellent bending resistance at high temperatures can be formed.

[0081] The polyester film may contain various additives within a range in which the total light transmittance is maintained within a preferred range. Examples of the additives include antistatic agents, UV absorbers, and stabilizers.

[0082] The total light transmittance of the polyester film is preferably 85% or more, more preferably 87% or more. If the transmittance is 85% or more, visual recognition can be fully ensured. It can be said that the higher the total light transmittance of the polyester film, the better, but from the perspective of stable production, it is preferably 99% or less, and can be 97% or less. The total light transmittance of the polyester film can be 85-99%, 85-97%, 87-99%, 87-97%.

[0083] The maximum thermal shrinkage of the polyester film after heat treatment at 150°C for 30 minutes can be 2% or less, preferably 1.5% or less, and more preferably 1.2% or less. If the maximum thermal shrinkage is 2% or less, the dimensional change caused by the heat release of the organic EL display itself can be suppressed. It can be said that the lower the maximum thermal shrinkage, the better, but it is preferably -1% or more, and preferably 0% or more. The negative value here means that expansion occurs after heating. When it is lower than -1%, it sometimes becomes poorly planar. The maximum thermal shrinkage of the polyester film after heat treatment at 150°C for 30 minutes can be -1 to 2%, -1 to 1.5%, -1 to 1.2%, 0 to 2%, 0 to 1.5%, 0 to 1.2%.

[0084] One or both surfaces of the polyester film of the present invention may be subjected to treatment for improving adhesion with a resin forming a hard coat layer or the like.

[0085] The treatment for improving adhesion may be, for example, a method of treating the surface of the polyester film, a method of providing an adhesion improving layer on the surface of the polyester film, etc. Examples of the method for treating the surface include sandblasting, roughening treatment by solvent treatment, etc., corona discharge treatment, electron beam irradiation treatment, plasma treatment, ozone and ultraviolet irradiation treatment, flame treatment, chromic acid treatment, hot air treatment, etc., and the surface treatment may be used without particular limitation.

[0086] In addition, by sandwiching an adhesion improving layer such as an easy-adhesion layer between the polyester film and the hard coating layer, the adhesion with the resin forming the hard coating layer etc. can also be improved. As the resin forming the easy-adhesion layer, acrylic resin, polyester resin, polyurethane resin, polyether resin etc. can be used without particular limitation, and the easy-adhesion layer can be formed by a common coating method, preferably a so-called in-line coating method.

[0087] The above-mentioned polyester film can be manufactured, for example, through the following steps: a polymerization step, in which the inorganic particles are uniformly dispersed in a monomer solution that becomes a part of the polyester raw material and filtered, and the inorganic particles that become a slurry are added to the remaining part of the polyester raw material to polymerize the polyester; and a film forming step, in which the polyester is melt-extruded into a sheet through a filter, and after cooling, it is stretched to form a substrate film.

[0088] Next, regarding the method for producing a biaxially stretched polyester film, an example of using pellets of polyethylene terephthalate (hereinafter, sometimes referred to as PET) as a raw material for a substrate film is described in detail, but the invention is not limited thereto. In addition, the number of layers such as a single-layer structure and a multi-layer structure is also not limited.

[0089] In addition, in the embodiment using polyethylene naphthalate (PEN) film instead of PET film, the polyester film of the present invention can also be produced by the same method.

[0090] After the PET pellets are mixed and dried in a predetermined ratio, they are supplied to a known melt lamination extruder, extruded from a slit-shaped die into a sheet, and cooled and solidified on a casting roll to form an unstretched film. In the case of manufacturing a single-layer film, an unstretched film can be formed by one extruder, and in the case of manufacturing a multi-layer film, two or more extruders, a multi-manifold or a confluence block (e.g., a confluence block with a square confluence portion) can be used to stack a plurality of film layers constituting each outermost layer, extrude a sheet of two or more layers from a nozzle, and cool it on a casting roll to form an unstretched film.

[0091] In the above case, during melt extrusion, it is preferred to perform high-precision filtration to remove foreign matter contained in the resin while the molten resin is maintained at an arbitrary position of about 300° C. The filter material used in the high-precision filtration of the molten resin is not particularly limited, and a filter material made of sintered stainless steel is preferred because it has excellent performance in removing aggregates and high-melting-point organic matter having Si, Ti, Sb, Ge, and Cu as main components.

[0092] Furthermore, the filter particle size (initial filtration efficiency 95%) of the filter material is preferably less than 20 μm, particularly preferably less than 15 μm. When the filter particle size (initial filtration efficiency 95%) of the filter material exceeds 20 μm, foreign matter larger than 20 μm cannot be fully removed. Although high-precision filtration of molten resin by using a filter material having a filter particle size (initial filtration efficiency 95%) of less than 20 μm may sometimes reduce productivity, it is preferred in terms of obtaining a film with fewer protrusions generated by coarse particles.

[0093] (About refractive index)

[0094] In the present invention, the refractive index of at least one of the longitudinal direction (mechanical flow direction) and the width direction of the polyester film is preferably 1.610 to 1.750, for example, 1.610 to 1.710, and more preferably 1.630 to 1.680. If the refractive index of at least one of the longitudinal direction and the width direction is 1.610 to 1.750, deformation during repeated folding is small, and there is no concern about reducing the image quality of the foldable display, which is preferred.

[0095] In one embodiment, the refractive index of the polyester film in the longitudinal direction is 1.610 or more, thereby effectively improving the crystallinity and the high temperature retention angle. If it is 1.750 or less, the stress during bending can be reduced, and the retention angle at room temperature and the high temperature retention angle can be improved.

[0096] Furthermore, unlike this embodiment, when the refractive index in the width direction of the polyester film is within the above range, it is desirable that the refractive index in the longitudinal direction of the polyester film is higher than the refractive index in the width direction of the polyester film.

[0097] The refractive index of the polyester film in the bending direction is preferably 1.610 to 1.750, for example 1.610 to 1.710, and more preferably 1.630 to 1.680. If the refractive index in the bending direction is 1.610 or more, the crystallinity can be efficiently improved and the high temperature holding angle can be improved. If the refractive index in the bending direction is 1.750 or less, the stress during bending can be reduced, and the holding angle at room temperature and the high temperature holding angle can be improved.

[0098] Here, the bending direction is Figure 2The direction indicated by reference numeral 22 on the polyester film (reference numeral 2) is a direction perpendicular to the folding portion (reference numeral 21) envisioned for use in a foldable display.

[0099] The refractive index of the polyester film in the bending direction is more preferably 1.630 to 1.680.

[0100] The refractive index of the polyester film can be effectively adjusted by adjusting the stretching ratio and the stretching temperature. In addition, in order to adjust the refractive index, a relaxation process and multi-stage stretching in the stretching direction can also be used. In the case of multi-stage stretching, it is preferred that the second stage and the subsequent stretching ratio are higher than the stretching ratio in the first stage.

[0101] By controlling the refractive index of at least one of the length direction (mechanical flow direction) and the width direction of the polyester film within the above range, and more preferably by controlling the refractive index of the bending direction within the above range, the fatigue caused by the compressive stress applied to the inner side of the fold during folding can be reduced. It is believed that the fatigue caused by the compressive stress mainly occurs in the crystal part, and when there are few crystals in the bending direction, fatigue is not easy. Therefore, the refractive index in the bending direction becomes smaller than the refractive index in the direction perpendicular to the bending direction, thereby reducing the amount of oriented crystals in the bending direction and suppressing the fatigue caused by the compressive stress.

[0102] In addition, by reducing the refractive index, the creep phenomenon caused by the tensile stress applied to the outside of the fold during folding can be suppressed. It is believed that fatigue caused by tensile stress mainly occurs in the amorphous part, and the molecular chains are aligned due to the repeated stress, resulting in deformation. It can be inferred that when there are fewer molecular chains arranged in the bending direction, the deformation caused by alignment is less. In addition, when there are fewer amorphous parts, fatigue caused by stretching can be suppressed, so it is preferred that the crystallinity, that is, the density, is high.

[0103] In the present invention, for the unstretched polyester sheet, the stretching ratio in at least one of the length direction (mechanical flow direction) and the width direction is preferably 1.0 to 3.4 times, and more preferably 1.4 to 2.3 times. Moreover, when the polyester film is used for a foldable display, the stretching direction given the ratio is preferably a bending direction. If the stretching ratio is 3.4 times or less, no uneven thickness of the film will occur, so it is preferred. As the stretching temperature, 120°C to 150°C is preferred, and 125°C to 145°C is more preferred. It should be noted that the heating method during stretching can adopt previously known means such as hot air heating, roller heating, infrared heating, etc. By setting the stretching temperature to 125°C to 145°C, large uneven thickness caused by stretching at the above-mentioned stretching ratio can be prevented.

[0104] (Refractive index in the folded direction)

[0105] The refractive index of the polyester film in a direction perpendicular to the direction in which the refractive index is 1.610 to 1.750 is preferably 1.750 to 1.870. For example, the refractive index of the bending direction of the polyester film is preferably 1.610 to 1.750, and the refractive index in the direction perpendicular to the bending direction (folding portion direction) is preferably 1.750 to 1.870. By setting the refractive index in the folding portion direction to 1.750 to 1.870, deformation during folding along the bending direction can be reduced. By setting the refractive index in the folding portion direction to 1.870 or less, cracks in the folding portion direction can be suppressed, and breakage can be further suppressed. In addition, breakage in the winding process after stretching can be suppressed. By setting the refractive index in the folding portion direction to 1.750 or more, the density of the polyester film can be increased, and the high temperature holding angle can be improved.

[0106] For example, when the longitudinal direction of the polyester film is the bending direction, the direction (folded portion direction) perpendicular to the bending direction corresponds to the width direction of the polyester film.

[0107] The refractive index in the direction perpendicular to the bending direction is more preferably 1.750 to 1.830.

[0108] In addition, when comparing the refractive index in the bending direction with the refractive index in the direction orthogonal to the bending direction (the folding direction), it is desirable that the refractive index in the bending direction is low. By making the refractive index in the bending direction lower than the refractive index in the folding direction, deformation during folding along the bending direction can be reduced. In addition, the occurrence of cracks in the folding direction can be suppressed, and fracture can be further suppressed. On this basis, fracture in the winding process after stretching can be suppressed. In addition, the density can be increased, and the high temperature holding angle can be improved.

[0109] As a method for adjusting the refractive index in the direction perpendicular to the bending direction, there can be cited methods of adjusting the stretching ratio in the direction, the stretching preheating temperature, the stretching temperature, the multi-stage stretching, the film relaxation, etc. The stretching ratio in the direction perpendicular to the bending direction is preferably 3.3 to 5.0 times, and more preferably 3.5 to 4.5 times. In addition, the stretching preheating temperature in the direction perpendicular to the bending direction is preferably 125 to 145°C. When multi-stage stretching is performed in a direction perpendicular to the bending direction, it is preferred that the stretching ratio in the second stage and thereafter is higher than the stretching ratio in the first stage. Film relaxation can be performed at 0 to 10% in any direction of the mechanical flow direction (length direction) and the perpendicular direction (width direction).

[0110] (Refractive index in the thickness direction)

[0111] The refractive index in the thickness direction is preferably 1.520 or less. It is more preferably 1.515 or less, further preferably 1.510 or less, particularly preferably 1.505 or less, and most preferably 1.500 or less. The refractive index in the thickness direction is preferably low, but in terms of stable production, it is preferably 1.300 or more, more preferably 1.400 or more, and particularly preferably 1.410 or more. The refractive index in the thickness direction may be 1.300 to 1.520, 1.300 to 1.515, 1.300 to 1.510, 1.300 to 1.500, 1.400 to 1.520, 1.400 to 1.515, 1.400 to 1.510, 1.400 to 1.500, 1.410 to 1.520, 1.410 to 1.515, 1.410 to 1.510, 1.410 to 1.500.

[0112] (About the density of polyester film)

[0113] The density of the polyester film is preferably 1.349 g / cm 3 More preferably 1.350 g / cm 3 By setting it to 1.349 g / cm 3 The density is also affected by the presence or absence of particles in the film, and is preferably 1.400 g / cm 3 Below, more preferably 1.395 g / cm 3 The density of polyester film can be 1.349 to 1.400 g / cm 3 1.349~1.395g / cm 3 1.350~1.400g / cm 3 1.350~1.395g / cm 3 .

[0114] The density of polyester film is 1.349g / cm 3 As described above, the crystallization of the polyester film of the present invention can be sufficiently advanced, and deformation at 85° C. can be suppressed. In addition, the heat shrinkage rate can be suppressed from increasing, and the dimensional change caused by heat generation of the device can be suppressed.

[0115] By setting the heat setting temperature during film formation to 210 to 270° C., crystallization proceeds, and the density can be effectively increased within the above range.

[0116] The bending direction of the polyester film preferably corresponds to the longitudinal direction (mechanical flow direction). In this way, the refractive index in the bending direction is easily reduced during biaxial stretching, and the bendability is easily improved. That is, by stretching the unstretched polyester sheet along the longitudinal direction at a stretching ratio of 1.0 to 3.5 times, preferably 1.0 to 3.3 times, and more preferably 1.0 to 2.4 times, a preferred polyester film can be obtained. Then, stretching along the width direction at a stretching ratio of 3.3 to 5.0 times, more preferably 3.5 to 4.5 times can be said to be a preferred method.

[0117] The polyester film of the present invention preferably has a high temperature retention angle of 100° or more at 60°C and a high temperature retention angle of 80° or more at 85°C in either the longitudinal direction or the width direction. Here, the high temperature retention angle refers to the angle of the fold produced when the polyester film is fixed under heating at a predetermined temperature (e.g., 60°C or 85°C) for 18 hours in a manner that a strain of 1.7% is produced on both surfaces of the bent portion.

[0118] The high temperature holding angle can be 101° or more, 102° or more under the heating condition of 60°C, and can be 81° or more, 82° or more under the heating condition of 85°C. The holding angle is preferably large, and 180° is most preferred. For example, 170° or less also has sufficient functions. The high temperature holding angle under the heating condition of 60°C can be 100-180°, 110-180°, 120-180°, 100-170°, 110-170°, 120-170°. The high temperature holding angle under the heating condition of 85°C can be 100-180°, 105-180°, 100-170°, 105-170°, 100-160°, 105-160°, 100-150°, 105-150°.

[0119] By keeping the high temperature holding angle within the above range, deformation at high temperature can be suppressed. In addition, the heat shrinkage rate can be suppressed from increasing, and the dimensional change of the polyester film caused by the heat release of the device can be suppressed. Therefore, according to the present invention, deformation after repeated folding is not easily caused in the high temperature area, and image disorder at the folded part of the display can be suppressed. Furthermore, a portable terminal device equipped with a foldable display using the polyester film of the present invention provides beautiful images, rich functionality, and excellent convenience such as mobility.

[0120] It should be noted that the method for measuring the high temperature holding angle in the bending direction is exemplified in the examples.

[0121] (Easy Adhesion Layer)

[0122] In order to improve the adhesion between the polyester film and the hard coating layer, etc., it is also preferred to laminate an easy-adhesive layer on at least one side of the polyester film of the present invention. The easy-adhesive layer can be obtained as follows: After applying the coating liquid for forming the easy-adhesive layer on one side or both sides of an unstretched or longitudinally uniaxially stretched film, heat treatment and drying are performed as needed, and further stretching is performed in at least one direction that has not been stretched, so as to obtain it. Heat treatment and drying can also be performed after biaxial stretching. The final coating amount of the easy-adhesive layer is preferably managed to be 0.005 to 0.20 g / m 2 If the coating amount is 0.005g / m 2 On the other hand, if the coating amount is 0.20 g / m 2 Below, the anti-blocking property is improved, which is preferred.

[0123] As the resin contained in the coating liquid used in the lamination of the easy-adhesive layer, for example, polyester resin, polyether polyurethane resin, polyester polyurethane resin, polycarbonate polyurethane resin, acrylic resin, etc. can be used without particular limitation. As the cross-linking agent contained in the coating liquid for forming the easy-adhesive layer, melamine compounds, isocyanate compounds, oxazoline compounds, epoxy compounds, carbodiimide compounds, etc. can be listed. Two or more kinds can be mixed and used respectively. They are preferably coated with water-based coating liquid in terms of the properties of online coating. The aforementioned resin and cross-linking agent are preferably water-soluble or water-dispersible resins or compounds.

[0124] In order to give the easy-adhesive layer easy slip, preferably add particles. The average particle size of the particles is preferably less than 2 μm. If the average particle size of the particles is less than 2 μm, the particles become difficult to fall off from the easy-adhesive layer. As the particles contained in the easy-adhesive layer, for example, inorganic particles such as titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silicon dioxide, aluminum oxide, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconium oxide, tungsten oxide, lithium fluoride, calcium fluoride, styrene-based, acrylic acid-based, melamine-based, benzoguanamine-based, silicone-based organic polymer-based particles, etc. can be listed. They can be added alone in the easy-adhesive layer, or two or more can be combined to add.

[0125] In addition, as the method of applying the coating solution for forming the easy-adhesive layer, a known method can be used. For example, reverse roll coating, gravure coating, kiss coating, roller brushing, spraying, air knife coating, wire rod coating, tubular scraper method, etc. can be listed, and these methods can be carried out alone or in combination.

[0126] (Hard Coating)

[0127] When the polyester film of the present invention is used as a surface protection film located on the surface of a foldable display to protect the display, it is preferred that at least one surface thereof has a hard coating layer. In the display, the hard coating layer is preferably located on the display surface side of the polyester film and used. As the resin forming the hard coating layer, resins such as acrylic acid, siloxane, inorganic mixture, urethane acrylate, polyester acrylate, and epoxy can be used without particular limitation. In addition, two or more materials can be used in combination, and particles such as inorganic fillers and organic fillers can also be added.

[0128] (Film thickness of hard coat layer)

[0129] The film thickness of the hard coating layer is preferably 1 to 50 μm. If it is 1 μm or more, it is fully cured and the pencil hardness becomes high, which is preferred. In addition, by making the thickness less than 50 μm, the curling caused by the curing shrinkage of the hard coating layer can be suppressed, and the operability of the film can be improved.

[0130] (Coating method)

[0131] As the coating method of the hard coat layer, a Meyer bar, a gravure coater, a rod coater, a knife coater, etc. can be used without particular limitation, and it can be appropriately selected according to the viscosity and the film thickness.

[0132] (Curing conditions)

[0133] As a method for curing the hard coat layer, curing methods using energy rays such as ultraviolet rays, electron beams, heat, etc. can be used. As a curing method, curing using energy rays such as ultraviolet rays, electron beams, etc. is preferred in order to reduce damage to the film.

[0134] (Pencil hardness)

[0135] The pencil hardness of the hard coating layer is preferably 3H or more, and more preferably 4H or more. If the pencil hardness is 3H or more, scratches are not easily caused, and visual recognition is not reduced. Generally, it is preferred that the pencil hardness of the hard coating layer is high, and it can be 9H or less, 8H or less, and even if it is 6H or less, it can be used without problems in practical use. The pencil hardness of the hard coating layer can be 3H to 9H, 3H to 8H, or 3H to 6H.

[0136] (Characteristics of hard coating)

[0137] The hard coat layer in the present invention can be used for the purpose of increasing the pencil hardness of the surface as described above and protecting the display, and preferably has a high transmittance. As a film having a hard coat layer (sometimes referred to as a hard coat film), the total light transmittance is preferably 87% or more, and more preferably 88% or more. If the total light transmittance is 87% or more, sufficient visual recognition is obtained. The total light transmittance of the hard coat film is generally higher, but for the sake of stable production, it can be 99% or less, or 97% or less. The total light transmittance of the hard coat film can be 87-99%, 88-99%, 87-98%, or 88-98%. In addition, the haze of the hard coat film is generally preferably low, preferably 3% or less. The haze of the hard coat film is more preferably 2% or less, and most preferably 1% or less. If the haze is 3% or less, the visual recognition of the image can be improved. For the sake of stable production, the haze is preferably 0.1% or more, and can be 0.3% or more. The haze of the hard coating film may be 0.1-3%, 0.1-2%, 0.1-1%, 0.3-3%, 0.3-2%, or 0.3-1%.

[0138] The hard coating layer may be further provided with other functions. For example, a hard coating layer provided with functions such as an anti-glare layer, an anti-glare anti-reflection layer, an anti-reflection layer, a low-reflection layer, and an antistatic layer having a constant pencil hardness as described above may be preferably applied to the present invention.

[0139] In addition, when used as a substrate film of a touch panel assembly, a hard coating layer may also be provided. For example, when an ITO layer is used as a transparent electrode layer of a touch panel assembly, the electrode pattern is not easily visible, and therefore, a refractive index adjustment layer is preferably provided between the substrate film and the transparent electrode layer. In this case, the hard coating layer itself may also serve as a refractive index adjustment layer, and further, a refractive index adjustment layer may be laminated separately.

[0140] In another embodiment, the polyester film of the present invention can be used as a back protective film for a foldable display. For example, the polyester film of the present invention can be arranged as a single back protective film that is continuous through the folded portion of the foldable display.

[0141] In another embodiment, a portable terminal device including the polyester foldable display of the present invention is provided.

[0142] Example

[0143] Next, the present invention will be described using examples and comparative examples. First, the following describes a method for determining characteristic values ​​implemented in the following examples.

[0144] (1) Intrinsic viscosity

[0145] The film or polyester resin is crushed and dried, and then dissolved in a mixed solvent of phenol / tetrachloroethane = 60 / 40 (mass ratio). The solution is centrifuged to remove inorganic particles, and then the flow time of a solution with a concentration of 0.4 (g / dl) and the flow time of only the solvent are measured at 30°C using an Ubbelohde viscometer. From their time ratio, the intrinsic viscosity is calculated using the Huggins formula, assuming that the Huggins constant is 0.38. The same calculation formula can be used for evaluation of polyethylene terephthalate (PET) and polyethylene naphthalate (PEN).

[0146] (2) Dynamic viscoelasticity measurement of polyester film

[0147] The measurement was carried out in a dynamic viscoelasticity measuring device "DMA7100" (manufactured by Hitachi High-Tech Corporation) in a tensile mode with a sample size of 8 mm in width and 20 mm in chuck spacing. The temperature was raised at 10°C / min at a frequency of 1 Hz and a measuring temperature of 25°C to 150°C. The tanδ value was calculated from tanδ=loss modulus / storage modulus, and the tanδ value was graphed, and the tanδ at 100°C was read from the graph.

[0148] (3) Refractive index of polyester film

[0149] A laser refractometer (model 2010 prism coupler) manufactured by Metricon was used to clamp a sample film under a pressure of 40 scales of the built-in pressure gauge, and the spectrum was obtained under a laser beam with a wavelength of 633nm. On the obtained spectrum, the point where the detector power dropped sharply was read and the value was taken as the refractive index. In the measurement mode TE, the refractive index in the length direction and the width direction was measured, and in the TM, the refractive index in the thickness direction was measured.

[0150] (4) Total light transmittance and haze of hard coating film

[0151] The total light transmittance and haze of the hard coating film were measured using a haze meter (NDH5000, manufactured by Nippon Denshoku Industries, Ltd.).

[0152] (5) Density of polyester film

[0153] The density of the polyester film was measured by the method based on JIS K-7112-1999 (density gradient tube method). (Unit: g / cm 3 ).

[0154] (6) Maximum thermal shrinkage of polyester film

[0155] Cut the sample film into 10mm in length and 250mm in width, align the long side with the direction to be measured, apply marks at intervals of 200mm, and measure the distance A (mm) between the marks under a constant tension of 5g. Next, place the sample film in an oven at 150°C for 30 minutes without load, take it out of the oven, and cool it to room temperature. After that, calculate the distance B (mm) between the marks under a constant tension of 5g, and calculate the thermal shrinkage rate (%) according to the following formula. It should be noted that the above-mentioned distance A and distance B are measured at three equal positions along the width direction of the sample film, and the average value of the distance A and distance B at the three points is taken as the thermal shrinkage rate (%).

[0156] Thermal shrinkage (%) = [(AB) × 100] / A

[0157] For the same film, the thermal shrinkage of the sample film with the bending direction as the long side and the thermal shrinkage of the sample film with the folded part direction (direction perpendicular to the bending direction) as the long side were measured, and the larger thermal shrinkage was taken as the maximum thermal shrinkage (%).

[0158] (7) High temperature holding angle

[0159] The angle of the folded line generated when the polyester film was fixed so as to apply a strain of 1.7% to both surfaces of the bent portion was measured.

[0160] Figure 3 This is a schematic diagram for illustrating the method of measuring the high temperature holding angle in the bending direction. The sample film (symbol 3) is cut into 10 mm in the width direction and 50 mm in the mechanical flow direction. A PTFE plate (symbol 32) as a spacer is clamped between two PTFE plates (symbol 31) to form a space. In the case of a 50 μm thick sample film, the thickness of the spacer is set to 3 mm. Double-sided tape is pasted on both ends of the sample film in the mechanical flow direction, and the film is clamped in a bent state in a 3 mm gap formed between two PTFE plates, and both ends are fixed to the two PTFE plates (symbol 31) with double-sided tape. After being placed in a dry environment at 60°C or 85°C for 18 hours, it is taken out from between the two PTFE plates (symbol 31), and after 5 minutes, the angle (symbol 33) of the crease generated in the film is measured. This angle is used as the high temperature holding angle.

[0161] In order to make the strain constant, the thickness of the PTFE plate used as a spacer was changed according to the thickness of the film (reference numeral 32).

[0162] Figure 4 Shown is sandwiched between two PTFE plates ( Figure 3 The enlarged schematic diagram of the sample film (symbol 3) in the state between the symbol 31). It should be noted that, Figure 4In the figure, symbol 41 is the diameter of the semicircle of the outermost surface of the sample film, symbol 42 is the diameter of the semicircle of the neutral plane of the sample film, and symbol 43 is the diameter of the semicircle of the innermost surface of the sample film. The neutral plane to which neither the compressive stress nor the tensile stress is applied is defined as the center in the thickness direction (dashed line in the figure), and the difference between the neutral plane and the two surfaces is defined as strain.

[0163] That is, in the evaluation of the high temperature holding angle, the strain (1.7%) can be expressed by the following method.

[0164] Strain (1.7%)

[0165] =(|semicircle of the outermost surface or the innermost surface - semicircle of the neutral surface| / semicircle of the neutral surface)×100 Here, the semicircle can be calculated from the thickness of the sample film t (mm), the bending diameter (the diameter of the outermost surface, that is, the thickness of the spacer used) d (mm), and the following formulas.

[0166] The semicircle of the outermost surface = d × π / 2

[0167] The semicircle of the neutral plane = (dt) × π / 2

[0168] The innermost semicircle = (d-2t) × π / 2

[0169] Based on the above, when the strain is set to 1.7%, the spacer thickness (mm) is determined from the sample film thickness t (mm) and the bending diameter (spacer thickness) d (mm) according to the following formula. The typical spacer thickness relative to the film thickness is expressed as follows.

[0170] Spacer thickness d (mm) = film thickness (mm) × 60

[0171] For example, in the case of the sample film having a thickness of 50 μm, the diameter of the outermost surface (symbol 41) is the same as the thickness d of the spacer, which is 3 mm. The diameter of the innermost surface (symbol 43) is 2.9 mm, and the diameter of the neutral plane (symbol 42) is 2.95 mm. Here, in the above formula representing strain, the semicircle of the outermost surface and the semicircle of the innermost surface can be appropriately selected.

[0172] Representative spacer thickness (d) relative to film thickness (t) are shown below.

[0173] Film thickness (t) Spacer thickness (d)

[0174]

[0175] (Preparation of polyethylene naphthalate (PEN) pellets)

[0176] Using 0.03 parts of manganese acetate tetrahydrate as an ester exchange catalyst, 100 parts of dimethyl naphthalene-2,6-dicarboxylate and 60 parts of ethylene glycol were slowly heated from 150°C to 238°C for 120 minutes. When the reaction temperature reached 170°C, trimethyl phosphate was added (in the form of a solution obtained by heating in ethylene glycol at 135°C, 5 hours, and under a pressure of 0.11 to 0.16 MPa: 0.023 parts in terms of trimethyl phosphate conversion). After the ester exchange reaction was completed, 0.024 parts of antimony trioxide were added. The reaction product was then transferred to a polymerization reactor, heated to 290°C, and polycondensed under a high vacuum of less than 27 Pa to obtain polyethylene 2,6-naphthalene dicarboxylate with an intrinsic viscosity of 0.48 dl / g and substantially free of particles.

[0177] (Preparation of polyethylene terephthalate (PET) pellets)

[0178] As the esterification reaction apparatus, a continuous esterification reaction apparatus composed of a stirring device, a partial condenser, and a three-stage complete mixing tank having a raw material inlet and a product outlet was used. TPA was 2 tons / hour, EG was 2 mol per 1 mol of TPA, and antimony trioxide was 160 ppm of Sb atoms relative to the produced PET. These slurries were continuously supplied to the first esterification reaction vessel of the esterification reaction apparatus, and reacted at 255° C. at an average residence time of 4 hours under normal pressure. Next, the reaction product in the first esterification reaction vessel was continuously taken out of the system and supplied to the second esterification reaction vessel. EG distilled from the first esterification reaction vessel was supplied to the second esterification reaction vessel in an amount of 8% by mass relative to the produced polymer (produced PET). Furthermore, an EG solution containing magnesium acetate in an amount of 65 ppm of Mg atoms relative to the produced PET and an EG solution containing TMPA in an amount of 20 ppm of P atoms relative to the produced PET were added, and reacted at 260° C. at an average residence time of 1.5 hours under normal pressure. Next, the reaction product in the second esterification reactor was continuously taken out of the system and supplied to the third esterification reactor, and an EG solution containing TMPA in an amount of 20 ppm of P atoms relative to the generated PET was further added, and the reaction was carried out at 260° C. under normal pressure with an average residence time of 0.5 hours. The esterification reaction product generated in the third esterification reactor was continuously supplied to a three-stage continuous polycondensation reaction device for polycondensation, and then filtered with a stainless steel sintered body filter (nominal filtration accuracy 5 μm particles 90% cutoff) to obtain polyethylene terephthalate pellets (a) with an intrinsic viscosity of 0.58 dl / g.

[0179] (Polymerization of urethane resin)

[0180] In a four-necked flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 72.96 parts by mass of 1,3-bis(isocyanatomethyl)cyclohexane, 12.60 parts by mass of dimethylolpropionic acid, 11.74 parts by mass of neopentyl glycol, 112.70 parts by mass of polycarbonate diol with a number average molecular weight of 2000, and 85.00 parts by mass of acetonitrile and 5.00 parts by mass of N-methylpyrrolidone as solvents were added, and stirred for 3 hours at 75°C under a nitrogen atmosphere to confirm that the reaction liquid reached the specified amine equivalent. Then, after cooling the reaction liquid to 40°C, 9.03 parts by mass of triethylamine was added to obtain a polyurethane prepolymer D solution. Next, 450 g of water was added to a reaction container equipped with a high-speed stirring homogenizer, and the temperature was adjusted to 25°C, while stirring at 2000 min. -1 The isocyanate group-terminated prepolymer was added while stirring and mixing to disperse in water. Then, acetonitrile and part of the water were removed under reduced pressure to prepare a water-soluble polyurethane resin (A) having a solid content of 35% by mass.

[0181] (Polymerization of water-soluble carbodiimide compounds)

[0182] In a flask equipped with a thermometer, a nitrogen inlet tube, a reflux condenser, a dropping funnel and a stirrer, 200 parts by mass of isophorone diisocyanate and 4 parts by mass of 3-methyl-1-phenyl-2-phospholene-1-oxide as a carbodiimidization catalyst were added, and stirred at 180° C. for 10 hours under a nitrogen atmosphere to obtain isocyanate-terminated isophorone carbodiimide (polymerization degree = 5). Then, 111.2 g of the obtained carbodiimide and 80 g of polyethylene glycol monomethyl ether (molecular weight 400) were reacted at 100° C. for 24 hours. Water was slowly added thereto at 50° C. to obtain a yellow transparent water-soluble carbodiimide compound (B) having a solid content of 40% by mass.

[0183] (Preparation of coating liquid for forming an easily adhesive layer)

[0184] The following coating materials were mixed to prepare a coating solution.

[0185]

[0186] (Silica sol with an average particle size of 40 nm and a solid content concentration of 40% by mass)

[0187] Surfactant 0.05 parts by mass

[0188] (Silicone-based, solid content concentration 100% by mass)

[0189] (Example 1)

[0190] Pellets of polyethylene naphthalate (PEN) are supplied to an extruder and melted at 310°C. The polymer is filtered through a filter material of a sintered stainless steel body (nominal filtration accuracy 10μm particles 95% cutoff), extruded from a nozzle into a sheet, and then, by an electrostatic casting method, brought into contact with a casting drum with a surface temperature of 60°C to cool and solidify, to prepare an unstretched film. The above-mentioned coating liquid for forming an easy-adhesion layer is applied on both sides of the unstretched film by a roller coating method, and then dried at 80°C for 20 seconds. It should be noted that the final coating amount after drying is 0.06g / m 2 After that, it was introduced into a tenter, preheated at 130°C, stretched transversely to 4.2 times at 135°C, fixed in width, heat fixed at 240°C for 5 seconds, and then relaxed by 1% in the width direction at 180°C, thereby forming a polyethylene naphthalate film with a thickness of 50 μm. The film was heated at 110°C for 24 hours and then restored to room temperature at 2°C / hour (BTA treatment) to obtain the films described in Tables 1 and 2. The film was subjected to various tests. The films obtained in other embodiments and comparative examples were also subjected to various tests in the same manner.

[0191] (Examples 2 to 4)

[0192] An unstretched film was obtained in the same manner as in Example 1. Before forming the easy-adhesion layer, the unstretched film was uniformly heated to 120° C. with a heating roller, and heated to 135° C. or 140° C. with a non-contact heater, and roller stretched (stretched in the longitudinal direction) at the stretching ratio in the longitudinal direction described in Table 1. Thereafter, a polyester film was obtained in the same manner as in Example 1 except that the temperature was set to the heat setting temperature described in Table 1.

[0193] (Example 5)

[0194] A polyester film was obtained by forming a film in the same manner as in Example 1 without performing a heat treatment (BTA treatment) after the film formation.

[0195] (Example 6)

[0196] A polyester film was obtained by forming a film in the same manner as in Example 3 without performing a heat treatment (BTA treatment) after the film formation.

[0197] (Example 7)

[0198] A polyester film was obtained in the same manner as in Example 4 except that the heating time in the heat treatment (BTA treatment) after film formation was changed to 12 hours.

[0199] (Example 8)

[0200] A polyester film was obtained in the same manner as in Example 4 except that the cooling rate to room temperature in the heat treatment (BTA treatment) after film formation was set to 20° C. / hour.

[0201] (Comparative Example 1)

[0202] Polyethylene terephthalate (PET) pellets were supplied to an extruder and melted at 285°C. The polymer was filtered with a stainless steel sintered filter (nominal filtration accuracy 10 μm particles 95% cutoff), extruded from a nozzle into a sheet, and then, by electrostatic casting, contacted with a casting drum with a surface temperature of 30°C to cool and solidify, to produce an unstretched film. The unstretched film was uniformly heated to 75°C with a heating roller, heated to 85°C with a non-contact heater, and subjected to 3.4 times roller stretching (length direction stretching).

[0203] The coating liquid for forming an easily adhesive layer was applied to both sides of the obtained uniaxially stretched film by roll coating, and then dried at 80° C. for 20 seconds. The final (after biaxial stretching) coating amount after drying was 0.06 g / m 2 After that, it was introduced into a tenter, preheated at 105°C, stretched to 4.0 times in the transverse direction at 95°C, fixed in width, heat fixed at 230°C for 5 seconds, and then relaxed by 4% in the width direction at 180°C, thereby forming a polyethylene terephthalate film with a thickness of 50 μm. The film was heated at 70°C for 24 hours and then returned to room temperature at 2°C / hour (BTA treatment), to obtain the films described in Tables 1 and 2.

[0204] (Comparative Example 2)

[0205] A polyester film was obtained in the same manner as in Comparative Example 1 except that the stretching ratio in the longitudinal direction was changed to 1.4 times.

[0206] (Comparative Example 3)

[0207] A polyester film was obtained in the same manner as in Example 4 except that the heating temperature in the heat treatment (BTA treatment) after film formation was set to 140° C. which is higher than the glass transition point.

[0208] (Comparative Example 4)

[0209] A polyester film was obtained in the same manner as in Example 4 except that the heating time in the heat treatment (BTA treatment) after film formation was 1 hour and the temperature control cooling time after heating was not taken and the film was immediately taken out of the heating oven to room temperature.

[0210] (Comparative Example 5)

[0211] Film formation was carried out in the same manner as in Example 4, except that heat treatment (BTA treatment) after film formation was not performed, thereby obtaining a polyester film.

[0212] The polyester films obtained in the examples and comparative examples were bonded to the non-visual recognition side of the organic EL element via a 25 μm thick adhesive layer to produce a smartphone-type foldable display that can be folded in half at the center of the entire display. Figure 1 The bending radius of the symbol 11 in the figure is 3 mm. The polyester film is arranged as a back protective film on the non-visual recognition side of a display that is continuous through the folded portion, and is attached to the polyimide film with a barrier layer as an organic EL substrate. The foldable display using the polyester film of each embodiment satisfies the movement and visual recognition of a portable smartphone that is folded in half at the center. In addition, there are no problems with movement and visual recognition at high temperatures.

[0213] On the other hand, for the polyester films of the comparative examples, in the foldable display used in the same manner, as the frequency of use at high temperature increases, the image deformation is felt to gradually occur at the folded portion of the display, which is not preferable. In addition, depressions and scratches are also confirmed on the surface of the folded portion.

[0214] [Table 1]

[0215]

[0216] [Table 2]

[0217]

[0218] Industrial Applicability

[0219] The foldable display using the polyester film for foldable display of the present invention maintains mass production, and does not cause deformation of the polyester film located on the back of the foldable display after repeated folding, so that the image disturbance at the folded part of the display does not occur. In particular, a portable terminal device or image display device equipped with a foldable display using the polyester film of the present invention as a back protective film provides beautiful images, is rich in functionality, has excellent convenience such as portability, and has high reliability.

[0220] Description of Reference Numerals

[0221] 1: Foldable display

[0222] 11: Bending radius

[0223] 2: Polyester film for foldable displays

[0224] 21: Folding part

[0225] 22: Bending direction (direction perpendicular to the folded portion)

[0226] 3: Sample film

[0227] 31: PTFE sheet

[0228] 32: Spacer

[0229] 33: Keep Angle

[0230] 41: The diameter of the outermost surface

[0231] 42: Diameter of the neutral plane

[0232] 43: The diameter of the innermost surface

[0233] 5. Foldable display

[0234] 51: Rear film

[0235] 52: Cover window (surface protection film)

[0236] 53: Polarizing plate / anti-reflection component

[0237] 54: Touch panel components

[0238] 55: Organic EL components

[0239] 56: Back protective film

[0240] 6: Outward-bending foldable smartphone

Claims

1. A polyester film, wherein tan δ at 100° C., as measured by dynamic viscoelasticity under tension, in at least one of a longitudinal direction and a width direction is 0.040 or less.

2. The polyester film according to claim 1, which has a thickness of 10 to 125 μm, a high temperature retention angle of 100° or more at 60°C and a high temperature retention angle of 80° or more at 85°C in either the longitudinal direction or the width direction, Here, the high temperature holding angle refers to the angle of the fold produced when the polyester film is fixed at 60° C. or 85° C. for 18 hours so that strain of 1.7% is produced on both surfaces of the bent portion.

3. The polyester film according to claim 1, which is used for a foldable display.

4. The polyester film according to claim 1, having a density of 1.349 g / cm 3 above.

5. The polyester film according to claim 1, wherein The polyester is polyethylene naphthalate. 6 . The polyester film for a foldable display according to claim 1 , comprising an easy-adhesion layer on at least one surface of the polyester film. 7 . A foldable display comprising the polyester film according to claim 1 , wherein the polyester film is arranged as a single back protective film that is continuous through a folded portion of the foldable display.

8. A portable terminal device comprising the foldable display according to claim 7.

Citation Information

Patent Citations

  • Method of processing hard coat film, hard coat film and protective film

    JP2010228391A

  • Manufacturing method for foldable hard coating film

    JP2016155124A

  • Polyester film and applications thereof

    WO2018150940A1